2009
DOI: 10.1097/md.0b013e3181a4d1a1
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Hypersensitivity Syndrome

Abstract: Drug-induced hypersensitivity syndrome (DIHS), also called drug rash with eosinophilia and systemic symptoms (DRESS), is a severe reaction usually characterized by fever, rash, and multiorgan failure, occurring 1-8 weeks after drug introduction. It is an immune-mediated reaction involving macrophage and T-lymphocyte activation and cytokine release, although no consensus has been reached as to its etiology. The skin, hematopoietic system, and liver are frequently involved. DIHS can mimic severe sepsis, viral in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(47 citation statements)
references
References 79 publications
1
43
0
3
Order By: Relevance
“…A careful assessment of the described DRESS cases in the literature revealed that the appearance of new symptoms is common in DRESS [10,11,12,13,14,15,16,17]. However, these were often labeled relapses linked to infectious complications and they were seldom recognized as new drug-elicited events.…”
Section: Mdh Dress and Flare-up Reactionsmentioning
confidence: 99%
“…A careful assessment of the described DRESS cases in the literature revealed that the appearance of new symptoms is common in DRESS [10,11,12,13,14,15,16,17]. However, these were often labeled relapses linked to infectious complications and they were seldom recognized as new drug-elicited events.…”
Section: Mdh Dress and Flare-up Reactionsmentioning
confidence: 99%
“…This is a systemic response, in which rash, mucosal involvement, atypical lymphocytes, frequent eosinophilia, and lymphadenopathy occur together with organ involvement (kidneys, liver, myocarditis/pericarditis). Treatment includes discontinuation of drug therapy and avoiding its use in the future and glucocorticoids for a short duration (6062). …”
mentioning
confidence: 99%
“…It is relevant that another anti-folate drug, sulphamethoxazoletrimethoprim, rarely causes DRESS (Drug rash with eosinophilia and systemic symptoms) 11 , which is an acute immune-mediated reaction causing macrophage and T-lymphocyte activation and cytokine release, reminiscent of drug-induced MAS.…”
Section: Discussionmentioning
confidence: 99%